2023
DOI: 10.1161/circresaha.122.322228
|View full text |Cite
|
Sign up to set email alerts
|

A Post-Pandemic Enigma: The Cardiovascular Impact of Post-Acute Sequelae of SARS-CoV-2

Abstract: COVID-19 has become the first modern-day pandemic of historic proportion, affecting >600 million individuals worldwide and causing >6.5 million deaths. While acute infection has had devastating consequences, postacute sequelae of SARS-CoV-2 infection appears to be a pandemic of its own, impacting up to one-third of survivors and often causing symptoms suggestive of cardiovascular phenomena. This review will highlight the suspected pathophysiology of postacute sequelae of SARS-CoV-2, its influence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 151 publications
(202 reference statements)
0
5
0
Order By: Relevance
“…In this review, cardiac imaging studies described cMRI abnormalities suggestive of myocardial scarring, sonographic sequelae, microvascular abnormalities per FMD scores or prior COVID infection as predictors of an abnormal SPECT‐MPI. Some studies propose that risk of myocarditis in the population with PASC appears to be lower than previously thought and suggest poor correlation with chest pain 10 . However, per one study, persistent cMRI cardiac abnormalities were found in 78% of patients irrespective of symptoms (87% patients were without chest pain at testing) at 2 weeks or later after infection and myocardial inflammation in 60% of patients 84 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this review, cardiac imaging studies described cMRI abnormalities suggestive of myocardial scarring, sonographic sequelae, microvascular abnormalities per FMD scores or prior COVID infection as predictors of an abnormal SPECT‐MPI. Some studies propose that risk of myocarditis in the population with PASC appears to be lower than previously thought and suggest poor correlation with chest pain 10 . However, per one study, persistent cMRI cardiac abnormalities were found in 78% of patients irrespective of symptoms (87% patients were without chest pain at testing) at 2 weeks or later after infection and myocardial inflammation in 60% of patients 84 .…”
Section: Discussionmentioning
confidence: 92%
“…About 48%–55.6% of patients affected by long COVID are women 2,3 . Importantly, persons identifying with racial and ethnic minority groups have not only a higher incidence of COVID‐19 acute infection/disease, hospitalization, morbidity, and mortality but also have been found to have a higher incidence of long COVID 9,10 . In addition, pregnant women are disproportionately affected with increased maternal and fetal morbidity due to the acute infection, and long COVID symptoms in pregnancy and their effects on their offsprings are under investigation 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…Third, based on virtually identical patterns of altered gene expression in mRNA vaccine associated myocardial injury and COVID-19 infection, these disorders may have a common pathobiology, related to the cellular response to Spike protein-ACE2 binding and internalization. 10,11 The reported incidence, consequences, and pathophysiology of post-acute sequelae of SARS-CoV-2 (PASC) are reviewed by Singh et al 12 Though the COVID-19 pandemic may be sundowning, its long-term effects are persisting in up to 20-25% of patients after COVID-19 infection; the precise incidence has been limited by varying definitions of PASC. Opposite to myocarditis, PASC seems to be associated with female gender, older age, and lack of SARS-CoV-2 vaccination, but not with severity of acute infection.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence, consequences, and pathophysiology of post-acute sequelae of SARS-CoV-2 (PASC) are reviewed by Singh et al 12 Though the COVID-19 pandemic may be sundowning, its long-term effects are persisting in up to 20-25% of patients after COVID-19 infection; the precise incidence has been limited by varying definitions of PASC. Opposite to myocarditis, PASC seems to be associated with female gender, older age, and lack of SARS-CoV-2 vaccination, but not with severity of acute infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation